Prima di Forum Cornelii: linguaggio figurativo e sincretismo culturale nella coroplastica dei santuari imolesi di età repubblicana - Manzelli, Valentina (O T I V M, 2024)
Some excavations in Imola area have allowed to recover meaningful data related to sanctuaries characterizing the moment during which Forum Cornelii became an important town. Analysis of votive and architectonic terracotta found in two different sacred extra urban contexts (Montericco and Pediano) has highlighted the direct influence of central Italy in the dedication of these worship places. Consequently, we can state that eastern Emilia was the result of an early phenomenon of Roman acculturation, made possible by building border sanctuaries already during the 3rd century b. C. Either it was a new foundation or the renovation of pre-existent local sanctuaries, the means of propaganda put into action was the figurative language. Such way of advertising was carried by handmade terracotta, which, in the 2nd cent. B.C. will show clear syncretism bearing witness that the insertion of the Italian component on the local substratum must have taken place in a pervasive and after all peaceful way.